UNDANG-UNDANG DAN PERATURAN ADAT: GAMBARAN SIKAP TOLERAN DAN KETERBUKAAN MASYARAKAT KALIMANTAN - Wasita, nfn (Naditira Widya, 2008)
Because of its variety characteristics, Indonesia has many potential conflicts. One of the reason of these conflicts is the feel of unsatisfied to government decision. History records some evidences of conflicts in Indonesia. Some are never finish and left as mysteries. But, history also records that some problems were solved. Archaeological remains such as the adat laws of Banjar and Kutai Kertanegara Sultanates, as well as ceremonies among Dayak Maanyan give us some reflections how past people in Kalimantan managed to solve some problems in community effectively. Can we apply the good practices in the past for now and future ?